The Concept of The Principle of Non Retroactive In Crime Human Rights In Indonesia - Nugrohadiputri, Diah Ayu Puspita; Tomy Michael (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This research analyzes how human rights cases are ressolved in Indonesia from the perspective of the concept of the non-retroactive principle. So far, regulations regarding the application of the concept of the non-retroactive principle have given rise to debate and views of the pros and cons. The method used is normative legal research. The approach take in this research uses a conceptual approach, cases, and legislation. Data collection in this research was carried out using library research to search for primary, secondary, tertiary legal materials. The results of this search indicate that the exception to the non-retroactive principle in cases of crimes against human rights in Indonesia is still insufficient. Many of the perpetrators of these crimes use the constitution or laws as a legal shield. At the another side, the slow court process in trying criminal cases that occured in the past is the result of factors in the legal system that were not developed seriously. This proves that the government